Saying Something about a Concept: Frege on Statements of Number. Issue 1 (2nd January 2021) - Textor, Mark
Abstract : The paper gives a historically informed reconstruction of Frege's view of statements of number. The reconstruction supports Frege's claim that a statement can be 'about a concept' although it does not contain a singular term referring to the concept. Hence, Frege's philosophy of number is not subject to the problems Frege sees for singular reference to concepts.